Legal Autopoiesis and the Capital/Revenue Distinction - Ding, Wai Boh (Victoria University of Wellington Law Review, 2007)
This paper attempts to use the theory of legal autopoiesis to understand the struggle the courts have experienced when asked to decide tax cases involving the capital/revenue distinction, which is a distinction that could not be determined by any criteria. The theory of legal autopoiesis, as propounded by Niklas Luhmann, posits that the legal system, as an autopoietic system within society, produces and reproduces its own elements self-referentially and recursively. The legal system operates according to its code, which comprises the values 'legal/illegal'. The code is complemented and filled by programmes, which must be suitable and help to allocate the values in particular situations. However, if there are no programmes, how does the legal system allocate the values? The lack of a definite set of rules that can be used in tax cases to determine whether an item is capital or revenue in nature means that there is no programme according to which the legal system can allocate the values. This lack exposes a critical weakness in Luhmann's theory of legal autopoiesis.